Respuesta :
Answer:
[tex]5\sqrt[3]{7}*y^3*x^{\frac{5}{3}}[/tex]
Step-by-step explanation:
We are asked to simplify the radical expression: [tex]\sqrt[3]{875x^5y^9}[/tex].
Using exponent rule for radical [tex]\sqrt[n]{ab} =\sqrt[n]{a}*\sqrt[n]{b}[/tex] we can rewrite our expression as:
[tex]\sqrt[3]{875x^5y^9}=\sqrt[3]{875}*\sqrt[3]{x^5}*\sqrt[3]{y^9}[/tex]
[tex]\sqrt[3]{875}=\sqrt[3]{125*7}=5\sqrt[3]{7}[/tex]
Using exponent rules for radical [tex]\sqrt[n]{a^m}=a^\frac{m}{n}[/tex] we will get,
[tex]\sqrt[3]{x^5}=(x^5)^{\frac{1}{3}}=x^{\frac{5}{3}}[/tex]
Using exponent rules for radical [tex]\sqrt[n]{a^m}=a^\frac{m}{n}[/tex] we will get,
[tex]\sqrt[3]{y^9}=(y^9)^3=y^{\frac{9}{3}}=y^3[/tex]
Upon substituting these values in our expression we will get,
[tex]\sqrt[3]{x^5}*\sqrt[3]{y^9}=5\sqrt[3]{7}*x^{\frac{5}{3}}*y^3[/tex]
Therefore, our radical expression simplifies to [tex]5\sqrt[3]{7}*y^3*x^{\frac{5}{3}}[/tex].
Answer:
5∛7 × [tex]x^{5/3}[/tex] × y³ is answer.
Step-by-step explanation:
we have to simplify the given expression 3√875x⁵y⁹
we use exponent rule for radical [tex]\sqrt[n]{xy} = \sqrt[n]{x} \sqrt[n]{y}[/tex]
we use this rule is this expression
3√875x⁵y⁹ = ∛875 × ∛x⁵ × ∛y⁹
∛875 = ∛125 ×7 = 5 ∛ 7
using exponent rule for radical [tex]\sqrt[n]{x^{m}}=x^{m/n}[/tex] we get
[tex]\sqrt[3]{x^{5} } =x^{5/3}[/tex]
similarly
[tex]\sqrt[3]{y^{9} } = y^{9/3}[/tex]
putting these values in given expression we get
3√875x⁵y⁹ = 5∛7 × [tex]x^{5/3}[/tex] × y³
therefore, our expression simplifies to 5∛7 ×[tex]x^{5/3}[/tex] × y³.